Plan de negocio para la creación de un centro de nutrición y estética - Ricaurte Paredes, César Andrés (2022)
The general objective of the study was to develop a business plan for the creation of a nutrition and aesthetics center in the city of Guayaquil in 2022. It is a field research of descriptive type and quantitative approach; a random probability sample of 190 women, urban area of Guayaquil between 20 and 54 years of age, who were applied a survey for data collection, analyzed quantitatively, was studied. Empirical methods are used: PESTEL and Five Forces of Competitiveness, accompanied by EFE, EFI and SWOT analysis matrices. The main results indicated an estimated potential demand of MMUSD 379,951; A required physical structure of 96 m2 for rent was considered and the equipment and materials necessary for the initial equipment were detailed. An organization of eight permanent posts and two contracted professional services was structured. Likewise, the marketing and promotion plan was structured to publicize the existence of the Center and attract customers. The initial investment is USD 24,059, the income budget for the first year of operations is USD 453,924 and the expenditure budget is USD 175,084. Under the conditions and parameters in which the business plan was developed, profitability was evaluated in a five-year spectrum resulting in a positive NPV, return on investment in the second year of operations and an IRR of 6%.